Leadership and knowledge management of the directors of the Higher Pedagogical Institute of Puno - Condori, Yeny (2019)
The objective of this work was to determine the degree of relationship between leadership and knowledge management of the directors of the Higher Pedagogical Institute of Puno, 2017. The research method was descriptive, corresponds to the correlational design, the technique used was the survey both variables and as a tool a questionnaire was applied. The statistical design for the hypothesis test was the Pearson correlation. The results indicate that there is a high degree of correlation between leadership and knowledge management. This conclusion is based on Pearson's statistical test, which is equal to 0.72, because the existence of a regular level of personal and institutional leadership makes it possible to have regular knowledge management levels of tangible capital and human resources.